W-DARE: a three-year program of participatory action research to improve the sexual and reproductive health of women with disabilities in the Philippines. (December 2015) - Vaughan, Cathy; Zayas, Jerome; Devine, Alexandra; Gill-Atkinson, Liz; Marella, Manjula; Garcia, Joy; Bisda, Krissy; Salgado, Joy; Sobritchea, Carolyn; Edmonds, Tanya; Baker, Sally; Marco, Ma.
Abstract Background In many contexts, women with disability have less access to sexual and reproductive health information, screening, prevention, and care services than women without disability. Women with disability are also known to be more likely to experience physical and sexual violence than women without disability. In the Philippines, health service providers often have little awareness of the sexual and reproductive experiences of women with disability and limited capacity to provide services in response to their needs. Very limited data are available to inform development of disability-inclusive sexual and reproductive health, and violence prevention and response, services in the country. This paper presents the protocol for W-DARE (Women with Disability taking Action on REproductive and sexual health), a three-year program of participatory action research that aims to improve the sexual and reproductive health of women with disability in the Philippines. Design W-DARE is a disability-inclusive program that will use mixed methods to 1) increase understanding of factors influencing the sexual and reproductive health of women with disability, and 2) develop, implement and evaluate local interventions to increase supply of and demand for services. W-DARE will generate data on the prevalence of disability in two districts; the wellbeing and community participation of people with and without disability, and identify barriers to community; and describe the sexual and reproductive health needs and experiences, and service-related experiences of women with disability. These data will inform the development and evaluation of interventions aiming to improve access to sexual and reproductive health services, and violence prevention and response services, for women with disability. Local women with disabilities, their representative organisations, and SRH service providers will be involved as members of the research team across all stages of the research. Discussion This three-year study will provide evidence about factors undermining the sexual and reproductive health of women with disability in a lower-middle income country, and provide new insights about what may be effective in increasing access to services in settings of limited resources. Findings will be relevant across Asia and the Pacific. Analysis of the program will also provide evidence about disability-inclusion in participatory action research approaches.